Puerarin hydrogel for promoting wound healing as well as preparation method and application of puerarin hydrogel

By co-assembling puerarin and calcium sulfate to form a two-component hydrogel, the problem of traditional dressings being unable to meet the wound healing moisture environment and lack of antibacterial and antioxidant is achieved, and efficient wound healing and safety is achieved.

CN119405650AActive Publication Date: 2025-02-11ZHEJIANG UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411548528.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-11
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

Traditional wound dressings cannot fully adapt to the moisture environment required for skin wound healing, and lack the inherent antibacterial and antioxidant abilities, making it difficult to effectively promote wound healing.

Method used

By co-assembling puerarin with calcium sulfate, a two-component molecular hydrogel is formed, and the mechanical properties of the gel are enhanced by cross-linked hydrogen bonds, and antibacterial and antioxidant properties are formed through hydrogen bonds between PUE and SO42-.

Benefits of technology

The high antioxidant performance, antibacterial performance and the function of promoting wound healing of hydrogels are achieved, which significantly improves the efficiency and safety of wound healing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119405650A_ABST
    Figure CN119405650A_ABST
Patent Text Reader

Abstract

The invention discloses puerarin hydrogel for promoting wound healing and a preparation method and application thereof.The puerarin hydrogel is prepared from puerarin and calcium sulfate, and the preparation method of the hydrogel comprises the steps that the puerarin and the calcium sulfate are added into water to be mixed to obtain a mixed solution, then the mixed solution is stirred at the high temperature to be clear and cooled at the room temperature, and the hydrogel is obtained. The content of puerarin is 2wt%, and the content of calcium sulfate is 0.08-0.2 wt%. Through compatibility of the radix puerariae and the gypsum, the mechanical property of the hydrogel is effectively improved, and the effect of promoting skin wound healing by the puerarin can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chronic wound infection treatment, and in particular relates to a puerarin hydrogel with a nanofiber network structure for promoting wound healing, a preparation method thereof, and an application thereof in skin wound healing. Background Art

[0002] Skin defects are very common in trauma and can lead to infection, serious complications, and even death. Conventional wound dressings commonly used in clinical practice include sterile dry gauze, oil-based gauze, cotton wool, etc. These dressings have different degrees of exudate absorption capacity to maintain a dry wound environment and prevent the invasion of harmful bacteria and other microorganisms that hinder wound healing. However, the healing of skin wounds is a complex process that requires a certain level of moisture to achieve optimal recovery. Traditional dressings cannot fully adapt to this requirement. Fortunately, with the advancement of materials science, new wound dressings such as 3D printed scaffolds, sponges, and hydrogels have been developed. Hydrogel materials not only establish an effective physical barrier within the wound, but also create a moist environment that is conducive to proper healing. Modern hydrogel dressings not only promote effective wound healing, but also reduce the frequency of dressing changes, thereby alleviating patient discomfort during these processes and reducing the clinical workload of healthcare.

[0003] The high swelling and breathability of hydrogels provide an optimal water environment for skin wound healing, promote adequate ventilation of skin cells, and offer new possibilities as wound dressings. Hydrogels can effectively form a physical barrier in wounds, create a moist environment, and promote effective wound healing. In addition, they can also be used as carriers to load other therapeutic drugs, such as antimicrobial agents or cytokines, to achieve multifunctional treatment. Previously, the antimicrobial properties of hydrogel dressings were mainly due to the presence of antibiotics in the hydrogel matrix or the addition of other antimicrobial substances. However, dressings with intrinsic antimicrobial activity are more desirable due to their consistent antimicrobial activity. Another challenge lies in the development of complex and cost-intensive wound dressings that promote wound healing by combining factors such as growth factors. Therefore, the inherent antimicrobial and antioxidant capabilities of wound dressings become very attractive.

[0004] Puerarin is the main bioactive ingredient of the traditional Chinese medicine Pueraria lobata, which is composed of hydrophilic glucose and hydrophobic isoflavones. Puerarin has multiple pharmacological activities and can self-assemble into hydrogels without modification, overcoming the limitations caused by its low hydrophilicity and bioavailability. However, the single network structure of puerarin hydrogel makes it mechanically weak and easy to disintegrate structurally. At the same time, Chinese herbal medicine (CHM) provides a huge wealth and source of inspiration for the development of innovative drug materials and treatment methods. Inspired by the macroscopic compatibility of Pueraria lobata and gypsum in CHM, the present invention co-assembles puerarin (PUE) and calcium sulfate (CaSO4) into a two-component molecular hydrogel. Importantly, the two-component gel has good biocompatibility, antibacterial and antioxidant properties, and can effectively promote wound healing. Summary of the invention

[0005] The purpose of the present invention is to solve the existing problems and provide a puerarin hydrogel for promoting wound healing, a preparation method and an application thereof. The hydrogel of the present invention has high antioxidant and antibacterial properties and the ability to promote wound healing.

[0006] In order to achieve these purposes and other advantages of the present invention, a hydrogel for promoting skin wound healing is provided, characterized in that the preparation method of the hydrogel is: puerarin and calcium sulfate are added to water and mixed to obtain a mixed solution, and then the mixed solution is stirred at a high temperature of 85 to 99° C. (further preferably, 88 to 92° C., and most preferably 90° C.) until it is clarified, and cooled at 20 to 30° C. to obtain the hydrogel.

[0007] Preferably, a hydrogel for promoting skin wound healing is made of the following raw materials in percentage by weight: 1-5% puerarin; 0.03-0.3% calcium sulfate; the balance is water. More preferably, 1.5-2.5% puerarin; 0.08-0.2% calcium sulfate; the balance is water. Most preferably, the content of puerarin is 2wt%, and the content of calcium sulfate is 0.08-0.2wt%.

[0008] The present invention also provides an application of a hydrogel in promoting skin wound healing, and an application of a hydrogel promoting skin wound healing in the preparation of a drug promoting skin wound healing. 2- Hydrogen bonds are formed between them, and a blue shift occurs after adding calcium sulfate, because PUE and SO4 2- The newly formed competitive hydrogen bonds between PUE molecules may be partially destroyed. In addition, after the addition of calcium sulfate, it was observed that the stretching vibration frequency of C=O in PUE also blue-shifted. At the same time, XRD results showed that the addition of calcium sulfate did not significantly change the local structure of the PUE component. The interaction between PUE and calcium sulfate enhanced the mechanical properties of puerarin hydrogel and promoted the effect of skin wound healing.

[0009] Advantages and beneficial effects of the present invention: Inspired by the macroscopic compatibility of pueraria root and gypsum in CHM, puerarin and calcium sulfate are co-assembled into a two-component molecular hydrogel. Compared with the single-component PUE gel, the mechanical properties of the two-component PUE gel are enhanced due to the introduction of cross-linked hydrogen bonds between PUE and CaSO4. Importantly, the two-component gel has good biocompatibility and antibacterial and antioxidant properties. In addition, the two-component gel has a good function of promoting wound healing. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 Schematic diagram of the gelation of hydrogels of Examples 1-4 of the present invention.

[0011] Figure 2 1 and 2 are SEM images and diameter distributions of hydrogels of Examples 1 to 4 of the present invention.

[0012] Figure 3 It is the infrared spectrum and X-ray diffraction diagram of the hydrogel of Example 1-4 of the present invention.

[0013] Figure 4 are G' and G" of the hydrogels of Examples 1-4 of the present invention at different strain amplitudes.

[0014] Figure 5 Graphs of G' and G" at different angular frequencies, viscosity at different shear rates and injectability of hydrogels of Examples 1-4 of the present invention.

[0015] Figure 6 The cytotoxicity and hemolysis rate of the hydrogels of Examples 1-4 of the present invention are shown.

[0016] Figure 7 This is the antibacterial property of the hydrogels of Examples 1-4 of the present invention.

[0017] Figure 8 is the free radical scavenging ability of the hydrogels of Examples 1-4 of the present invention.

[0018] Fig. 9 It is a graph showing the wound healing effect of the hydrogels of Examples 1-4 of the present invention on mice.

[0019] Fig.10 This is a histopathological staining analysis of mouse wound healing using the hydrogels of Examples 1-4 of the present invention.

[0020] Fig.11 The present invention is a schematic flow chart of a method for preparing a hydrogel for promoting skin wound healing. DETAILED DESCRIPTION

[0021] In order to further illustrate the present invention, the preparation and application of the supramolecular hydrogel with a nanofiber network structure of the present invention are described in detail below with reference to the examples.

[0022] Example 1 PUE hydrogel

[0023] The hydrogel of this embodiment is prepared from the following raw materials by mass fraction:

[0024] Isoflavones: puerarin 2wt%;

[0025] The balance is water.

[0026] Preparation method:

[0027] According to the raw material formula, the weighed puerarin was first added into deionized water, stirred at 90°C for 15 min until the puerarin was completely dissolved, and then cooled at room temperature (25°C) to form a gel, which was recorded as PUE hydrogel.

[0028] Example 2 PCa-1 hydrogel

[0029] The hydrogel of this embodiment is prepared from the following raw materials by mass fraction:

[0030] Isoflavones: puerarin 2wt%;

[0031] Calcium sulfate: 0.0825wt%;

[0032] The balance is water.

[0033] Preparation method:

[0034] According to the raw material formula, weighed puerarin and calcium sulfate were first added into deionized water, stirred at 90°C for 15 min until puerarin was completely dissolved, and cooled at room temperature (25°C) to form a gel, which was recorded as PCa-1 hydrogel.

[0035] Example 3 PCa-2 hydrogel

[0036] The hydrogel of this embodiment is prepared from the following raw materials by mass fraction:

[0037] Isoflavones: puerarin 2wt%;

[0038] Calcium sulfate: 0.165wt%;

[0039] The balance is water.

[0040] Preparation method:

[0041] According to the raw material formula, weighed puerarin and calcium sulfate were first added into deionized water, stirred at 90°C for 15 min until puerarin was completely dissolved, and cooled at room temperature 25°C to form a gel, which was recorded as PCa-2 hydrogel.

[0042] Example 4 PCa-3 hydrogel

[0043] The hydrogel of this embodiment is prepared from the following raw materials by mass fraction:

[0044] Isoflavones: puerarin 2wt%;

[0045] Calcium sulfate: 0.2wt%;

[0046] The balance is water.

[0047] Preparation method:

[0048] According to the raw material formula, weighed puerarin and calcium sulfate were first added into deionized water, stirred at 90°C for 15 min until puerarin was completely dissolved, and cooled at room temperature (25°C) to form a gel, which was recorded as PCa-3 hydrogel.

[0049] The gelation results of the supramolecular hydrogel with nanofiber network structure prepared in Examples 1-4 are as follows: Figure 1 shown.

[0050] 1. Experimental Characterization

[0051] 1.1 Fiber morphology

[0052] The effect of calcium sulfate on the gel morphology was observed by scanning electron microscopy. Figure 2 As shown in Figure e (i.e., Example 1), the dry gel of PUE presents a typical dense and fibrous structure with an average diameter of 57 nm. Figure 2 f (i.e., Example 2), for PCa-1 gel, the addition of a small amount of calcium sulfate causes the nanofibers to become thinner, with a diameter reduced to 36 nm. The reduction in nanofiber diameter can be attributed to SO4 2- The hydrogen bonds formed between the -OH groups will affect the bundling of the nanofibers during their three-dimensional growth. However, further addition of calcium sulfate leads to thickening of the gel fibers, with PCa-2 (i.e., Example 3) and PCa-3 (i.e., Example 4) being as shown in FIG. Figure 2 g and 2h. The increase in the diameter of the gel nanofibers can be explained by the fact that more SO4 2- More hydrogen bonds are generated, thus connecting more bundles of gel nanofibers laterally. In summary, the SEM data showed that the morphology of the gel network remained almost the same, but with nanofibers of different diameters depending on the amount of calcium sulfate added.

[0053] 1.2 FTIR spectral analysis

[0054] like Figure 3 As shown, PUE dry gel at 3320 cm -1 The broad stretching vibration of -OH is shown at 3340 cm-1. With the increase of calcium sulfate content, the stretching vibration of -OH of PCa-1, PCa-2 and PCa-3 blue-shifts to 3340 cm-1, 3340 cm-2 and 3340 cm-3, respectively. -1 、3349cm-1 and 3407cm -1 This blue shift behavior indicates that due to the PUE and SO4 2- The newly formed competitive hydrogen bonds between the PUE molecules may be partially destroyed. In addition, after the addition of calcium sulfate, it was observed that the stretching vibration frequency of C=O in PUE also blue-shifted (from 1695cm -1 to 1698cm in PCa-1, PCa-2, and PCa-3 -1 ). It is reported that the C=O···π interaction is the main driving force for the assembly of PUE molecules into gel networks. Here, the blue shift of the C=O stretching vibration frequency induced by CaSO4 indicates that the -OH of PUE binds to SO4 2- Hydrogen bonds are formed between them, and the C=O···π interaction between PUE molecules may also be partially disturbed.

[0055] 1.3 X-ray diffraction

[0056] like Figure 3 As shown in Figure 2, for the PUE xerogel sample, a broad diffraction peak centered at 20° indicates the amorphous nature of the PUE gel structure. The corresponding spacing is calculated as This is probably due to the presence of C=O···π interactions. After adding calcium sulfate, PCa-1, PCa-2, and PCa-3 xerogel samples all showed similar diffraction patterns, especially their diffraction spectra were just the overlap of pure PUE and calcium sulfate diffraction. This result suggests that the addition of calcium sulfate did not significantly change the local structure of the PUE assembly, and assuming that SO4 2- are adsorbed on the periphery of the PUE components rather than inserted into the layered and assembled PUE molecules.

[0057] 1.4 Rheological test

[0058] We performed rheological measurements and first used the strain sweep mode to probe the linear viscoelastic region of the hydrogel. The sweep frequency was kept at 1 Hz and the strain range was 0.01–10%. Figure 4 As shown, the storage modulus (G') of the four hydrogels is higher than the loss modulus (G") when the strain does not exceed 10%. Compared with the PUE hydrogel, all CaSO4-containing gels show higher yield strain points.

[0059] At the same time, Figure 5Angular frequency sweeps between 0.01 and 100 rad / s revealed that G’ for all gels was also greater than G”, illustrating the gel nature of these samples. All gels containing CaSO4 had higher G’ than the PUE gels. These rheological tests indicate that the addition of calcium sulfate can increase the crosslinking density, thereby improving the mechanical properties of the hydrogels. In addition, we found that the viscosity of all hydrogels decreased with increasing shear rate, indicating that these hydrogels have shear-thinning properties and can be used as injectable materials. This injectability is believed to be mainly due to the presence of dynamic non-covalent interactions in the gel network.

[0060] 1.5 Biocompatibility

[0061] like Figure 6 As shown in a, the survival rate of L929 cells after incubation with PUE, PCa-1, PCa-2 and PCa-3 hydrogels for 4 days remained above 85%, indicating that all these gels have very low cytotoxicity. Figure 6 Live / dead cell staining experiments in c showed that L929 cells in the control group and hydrogel group showed spindle morphology after 1, 2, and 4 days, with almost no cell death (red), further confirming the good biocompatibility of the hydrogel.

[0062] Blood compatibility is another important prerequisite for the application of biomaterials in wound healing, because wound dressings can directly contact the blood at the wound site. Figure 6 As shown in b, there is a significant color difference between all the light yellow hydrogel groups and the positive control (deionized water) group. Quantitative analysis showed that the hemolysis rates of PCa-1, PCa-2, and PCa-3 hydrogels were lower than the internationally recognized 5% standard, while the hemolysis rate of PUE hydrogel exceeded this threshold, indicating that all PCa hydrogels except PUE hydrogel have good blood compatibility.

[0063] 1.6 In vitro antibacterial and antioxidant efficacy

[0064] The present invention uses Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli as model strains to evaluate the antibacterial activity of the hydrogel. The optical density (OD 600 ) to determine the bacterial growth curve, which provides a basis for understanding the antibacterial properties of hydrogels. Figure 5 As shown in Figures 5b and 5c, compared with the control group, the PUE, PCa-1, PCa-2, and PCa-3 groups all had an inhibitory effect on the growth of both strains, while the calcium sulfate group did not have any antibacterial effect. In addition, the antibacterial properties of the hydrogels were further evaluated by performing experiments on plates. Compared with the blank group and the calcium sulfate group, the PUE, PCa-1, PCa-2, and PCa-3 gel groups had antibacterial activity against Staphylococcus aureus and Escherichia coli.

[0065] We then proceeded to evaluate the antioxidant function of these hydrogels. The antioxidant activity of PUE, PCa-1, PCa-2, and PCa-3 hydrogels was evaluated by measuring the scavenging rates of DPPH and ABTS free radicals. Figure 8 a and 8b. The scavenging ability of the hydrogel at 1 mg / mL (based on PUE concentration) for DPPH and ABTS was weak, and when the PUE concentration reached 3 mg / mL, more than 80% of DPPH and 91% of ABTS free radicals were scavenged.

[0066] 1.7 In vivo wound healing

[0067] The PCa hydrogel had good biocompatibility, antibacterial and antioxidant effects in vitro, and a full-thickness wound model of Escherichia coli infection in rats was established to further evaluate its in vivo wound healing effect. The wounds of each group were photographed on days 0, 1, 3, 6, and 10, and the wound area was quantified. After 1 day of treatment, yellow pustules appeared on the wound site of the blank group, indicating that the skin defect model infected with Escherichia coli was successfully established. On the 3rd day, the wound area of ​​all 6 treatment groups decreased. As the healing process was extended to the 10th day, the wounds of Tegadrem, PUE, PCa-1, PCa-2, and PCa-3 groups were completely closed and healed, while the wounds of the blank group were still obvious and large. Quantitatively, there were no significant differences among the treatments of Tegadrem, PUE, PCa-1, PCa-2, and PCa-3, and the wound closure rates were 95.32%, 90.34%, 89.94%, 90.50%, and 91.08%, respectively, which were significantly higher than those of the blank group, indicating that PCa hydrogel exhibited effective wound healing ability.

[0068] 1.8 Histological analysis

[0069] We performed histological and immunological analyses to further understand the process of wound healing, e.g. Fig.10 The H&E staining results of a showed that the formation of granulation tissue in each group was significantly impaired on day 5. The collagen density in the granulation tissue of the PCa-2 group and the Tagaderm group was higher than that of the blank control group, and the number of inflammatory cells was also lower than that of the blank control group. By day 10, the dermis of the blank control group was obviously not healed, while the epidermis of the PCa-2 group and the PCa-3 group was relatively completely regenerated, with obvious hair follicles and sebaceous glands near the incision. Fig.10 The Masson staining results in b also showed that the collagen arrangement on the wound surface of the PCa-2 and PCa-3 groups was very similar to that of normal cells, accompanied by more complete epidermal regeneration.

[0070] In summary, PUE / CaSO4 gel has good biocompatibility and antibacterial and antioxidant properties. In addition, the results from the Escherichia coli infected mouse wound model showed that PUE / CaSO4 hydrogel has the property of effectively promoting wound healing and has good application prospects.

[0071] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and implementation modes. They can be fully adapted to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.

Claims

1. A puerarin hydrogel for promoting wound healing, characterized in that: Made from the following raw materials in percentage by mass: Puerarin 1-5%; Calcium sulfate 0.03-0.3%; Water balance.

2. The puerarin hydrogel for promoting wound healing according to claim 1, characterized in that: Made from the following raw materials in percentage by mass: Puerarin 1.5-2.5%; Calcium sulfate 0.08-0.2%; Water balance.

3. The method for preparing the puerarin hydrogel for promoting wound healing according to claim 1 or 2, characterized in that: The following steps are involved: Puerarin and calcium sulfate are added into water and mixed to obtain a mixed solution, and then the mixed solution is stirred at a high temperature of 85-99° C. until it becomes clear, and cooled to obtain a puerarin hydrogel that promotes wound healing.

4. The method for preparing the puerarin hydrogel for promoting wound healing according to claim 3, characterized in that: The mixed solution was stirred at a high temperature of 88-92°C until it became clear.

5. The method for preparing the puerarin hydrogel for promoting wound healing according to claim 3, characterized in that: Cool at 20-30℃.

6. Use of the puerarin hydrogel for promoting wound healing as claimed in claim 1 or 2 in the preparation of a drug for promoting skin wound healing.

Citation Information

Patent Citations

  • Hydrogel dressing band-aid for diabetic wounds and application of hydrogel dressing band-aid

    CN116474154A

  • Preparation method and coating application of self-healing and antibacterial dynamic hydrogel

    CN117618643A

  • Hydrogel composite material for repairing myocardial infarction as well as preparation method and application of hydrogel composite material

    CN118105539A

  • Multifunctional nano hydrogel as well as preparation method, verification method and application thereof

    CN118593418A

  • Polymer formulations for delivery of bioactive agents

    US20110033540A1